University Spin-offs in the Business Transformation of the University of the Century - Armando José Urdaneta Montiel; Bladimir Jaramillo Escobar; Gina Pamela Moyano Morán (Eduser)
University spin-offs play a crucial role in the business vision of the postmodern university by generating technological products and intellectual property, allowing the articulation among the academia, the public sector and the society. The research aimed to determine the validity of university spin-offs and the role they play in the generation of innovation, development of science and technology transfer. The study is qualitative, based on documentary sources of specialized articles in indexed databases, of which 26 were selected based on criteria related to the topic, successful experiences in the creation and operation of these companies. The content analysis technique was used with emphasis on argumentation, narration and enunciation. Among the main results, it can be mentioned that university spin-offs play an important role as means for technology transfer, however, they require improving and innovating management, organizational structure and institutional culture. Furthermore, a regulatory framework is needed in order to promote the operation of these entities and to strengthen the relationship and cooperation among the university, the State and the business sector. The adoption of an entrepreneurial mindset in universities, both public and private, is essential to improve competitiveness and support teaching, research.